Reliability of Goniometric Techniques for Measuring Hip Flexor Length Using the Modified Thomas Test - Kira Eimiller; Emma Stoddard; Briana Janes; Mason Smith; Andrew Vincek (International Journal of Sports Physical Therapy)
# Background